INTERFERENSI DAN STRATEGI PENERJEMAHAN LISAN PADA AKTIVITAS LUAR KELAS MAHASISWA PROGRAM STUDI SASTRA JEPANG UNIVERSITAS DIAN NUSWANTORO - Bayu Aryanto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
The research is descriptive research about the interference of foreign language and direct translation technique of Udinus Japanese Literature students class 2010. This research purpose to discover the interference of foreign language and technique which is being used in translation process. The data source of this thesis is Udinus Japanese Literature students class 2010’s interpreting audio and video. The result of data can befound two types of interference. First type is Indonesia interference, second type is English interference. Furthermore, there aresome technique which is being used during translation process. They are reduction technique, addition technique, and quotation techniqueKeywords: interferensi, terjemahan lisan, teknik penerjemahan, tuturan sumber, interferensi